Odpowiedź :
a) 2log5 + log4=log5²+log4=log25+log4=log(25*4)=log100, zatem mamy 10^(x)=100, zatem x=2
10^(x) - dziesięć do potęgi x
b) 2log₃(6) - log₃(4) =log₃6²-log₃4=log₃36-log₃4=log₃(36:4)=log₃9 czyli 3^(x)=9 zatem x=2
c) log ₄(40) - log ₄(5)=log₄(40:5)=log₄8
zatem 4^(x)=8, zatem (2²)^x=2³, czyli 2^(2x)=2³ czyli 2x=3, zatem x=(3/2)
d) log₄(3) - log₄(48) =log₄(3/48)=log₄(1/16)
czyli 4^(x)=1/16, zatem 4^(x)=4⁻2, zatem x=-2
e) log₅(0,5) + 2log₅(20) - 3log₅(2)=
log₅(0,5)+log₅(20²)-log₅(2³)=log₅(0,5*400)-log₅8=
log₅(200)-log₅8=log₅(200:8)=log₅25 zatem 5^(x)=25, a 5^(x)=5², zatem x=2.
:)
10^(x) - dziesięć do potęgi x
b) 2log₃(6) - log₃(4) =log₃6²-log₃4=log₃36-log₃4=log₃(36:4)=log₃9 czyli 3^(x)=9 zatem x=2
c) log ₄(40) - log ₄(5)=log₄(40:5)=log₄8
zatem 4^(x)=8, zatem (2²)^x=2³, czyli 2^(2x)=2³ czyli 2x=3, zatem x=(3/2)
d) log₄(3) - log₄(48) =log₄(3/48)=log₄(1/16)
czyli 4^(x)=1/16, zatem 4^(x)=4⁻2, zatem x=-2
e) log₅(0,5) + 2log₅(20) - 3log₅(2)=
log₅(0,5)+log₅(20²)-log₅(2³)=log₅(0,5*400)-log₅8=
log₅(200)-log₅8=log₅(200:8)=log₅25 zatem 5^(x)=25, a 5^(x)=5², zatem x=2.
:)
a) 2log5 + log4=
=log5²+log4=
=log25+log4=
=log(25*4)=
=log100,
mamy 10^x=100, 10^x - czyli 10 do pot x
czyli x=2
b) 2log₃(6) - log₃(4) =
=log₃6²-log₃4=
=log₃36-log₃4=
=log₃(36:4)=
=log₃9
czyli 3^(x)=9
3^x=3^2
mamy x=2
c) log ₄(40) - log ₄(5)=
=log₄(40:5)=
=log₄8
zatem 4^(x)=8,
czyli (2²)^x=2³,
2^(2x)=2³
2x=3,
x=(3/2)
d) log₄(3) - log₄(48) =
log₄(3/48)=
=log₄(1/16)
czyli 4^(x)=1/16,
zatem 4^(x)=4⁻2,
x=-2
e) log₅(0,5) + 2log₅(20) - 3log₅(2)=
=log₅(0,5)+log₅(20²)-log₅(2³)=
=log₅(0,5*400)-log₅8=
=log₅(200)-log₅8=
=log₅(200:8)=log₅25
zatem 5^(x)=25,
5^(x)=5²,
x=2.
=log5²+log4=
=log25+log4=
=log(25*4)=
=log100,
mamy 10^x=100, 10^x - czyli 10 do pot x
czyli x=2
b) 2log₃(6) - log₃(4) =
=log₃6²-log₃4=
=log₃36-log₃4=
=log₃(36:4)=
=log₃9
czyli 3^(x)=9
3^x=3^2
mamy x=2
c) log ₄(40) - log ₄(5)=
=log₄(40:5)=
=log₄8
zatem 4^(x)=8,
czyli (2²)^x=2³,
2^(2x)=2³
2x=3,
x=(3/2)
d) log₄(3) - log₄(48) =
log₄(3/48)=
=log₄(1/16)
czyli 4^(x)=1/16,
zatem 4^(x)=4⁻2,
x=-2
e) log₅(0,5) + 2log₅(20) - 3log₅(2)=
=log₅(0,5)+log₅(20²)-log₅(2³)=
=log₅(0,5*400)-log₅8=
=log₅(200)-log₅8=
=log₅(200:8)=log₅25
zatem 5^(x)=25,
5^(x)=5²,
x=2.